A document in madness: a study on the insanity of Shakespeare’s Ophelia (Palíndromo, 2020)
The chief aim of this paper is to analyse the character of Ophelia, from William Shakespeare’s Hamlet. By investigating the elements in the play that are most significant to her character, this study seeks to assess the factors that, woven together, culminated into her madness. The main aspects to be studied are the characters that are closest to her, such as Polonius, Laertes and Hamlet, the challenges of her role as a woman, a daughter and a potential lover, and the abiding influence of the late King Hamlet in the play’s events.
Keywords: William Shakespeare; Ophelia; Hamlet; madness